2009
DOI: 10.1016/j.urology.2009.04.090
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Bladder Cancer With Microelectromechanical Systems-based Cystoscopic Optical Coherence Tomography

Abstract: Purpose-We examined the utility and potential limitations of MEMS (Microelectro-mechanical systems) based spectral-domain cystoscopic optical coherence tomography (COCT) to improve the diagnosis of early bladder cancer.Materials and Methods-OCT catheter was integrated into the single instrument channel of a 22Fr cystoscope to permit white-light guided COCT over a large field of view of 4.6mm wide and 2.1mm deep per scan at 8 frames/s and 10um resolution. Intraoperative COCT diagnosis was performed in 56 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 15 publications
0
39
0
Order By: Relevance
“…The diseased regions were created using an excise-and-fill method, similar to a previously described process [16]; small sections of the phantom were excised during various steps of the fabrication process and then filled with Dragon Skin, the properties of which depended on the desired end diseased state. A brief overview of the relevant diseased states follows stemming from insights published in literature [7,9,10,24]. Pre-cancerous dysplastic lesions manifest as a thickening of the uroltheliem, appear flat under WLC, and do not exhibit fluorescent contrast under BLC.…”
Section: Phantom Fabricationmentioning
confidence: 99%
See 1 more Smart Citation
“…The diseased regions were created using an excise-and-fill method, similar to a previously described process [16]; small sections of the phantom were excised during various steps of the fabrication process and then filled with Dragon Skin, the properties of which depended on the desired end diseased state. A brief overview of the relevant diseased states follows stemming from insights published in literature [7,9,10,24]. Pre-cancerous dysplastic lesions manifest as a thickening of the uroltheliem, appear flat under WLC, and do not exhibit fluorescent contrast under BLC.…”
Section: Phantom Fabricationmentioning
confidence: 99%
“…Recently, OCT and BLC have shown great promise as adjunct technologies to traditional WLC for bladder cancer detection [6][7][8][9][10]. A hurdle in the development and testing of new imaging technologies, however, is the lack of a large animal model for bladder cancer to yield diseased samples of reasonable size.…”
Section: Introductionmentioning
confidence: 99%
“…Of the 45 studies, only 9 met the inclusion criteria and were considered suitable for inclusion in the meta-analysis for OCT and bladder cancer ( Fig. 1) (4,(17)(18)(19)(20)(21)(22)(23)(24). All the eligible studies were published between 2002 and 2014.…”
Section: Resultsmentioning
confidence: 99%
“…Recent technological advances have enabled real-time two-dimensional (2D) and three-dimensional (3D) OCT imaging, Doppler OCT for functional subsurface blood flow imaging, ultrahigh-resolution OCT for subcellular imaging, and endoscopic OCT for noninvasive imaging of various internal organs. [8][9][10] Meanwhile, preclinical and clinical studies have demonstrated the utility of OCT in delineating morphological details of biological tissues (e.g., skin, oral cavity, esophagus, colon, bladder, and cervix), [11][12][13] and thus the potential for detecting cancers in these organs.…”
Section: Introductionmentioning
confidence: 99%
“…While our recent human study showed the clinical feasibility of our endoscopic OCT to significantly enhance early bladder cancer diagnosis, 10 here we present a pilot feasibility study on fresh human fetal membrane specimens from normal controls and from patients with MCP to explore the potential of OCT for early detection of pathological changes, which might serve in the prediction of preeclampsia or other diseases associated with pregnancy. We compare the image results of OCT and high-frequency ultrasound (HFUS) with the corresponding histological counterparts (clinical standard), so that the utility and potential limitations of OCT for high-resolution delineation of the morphology of human FMs and identification of pathological changes can be examined.…”
Section: Introductionmentioning
confidence: 99%